Flash-DBSim: A simulation tool for evaluating Flash-based database algorithms - Xuan Su; Peiquan Jin; Xiaoyan Xiang; Kai Cui; Lihua Yue (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
Flash memory is becoming an attractive alternative to traditional hard disks, because of its small-size, shock-resistant, power-economic, and non-volatile natures. In order to utilize the special I/O properties of flash disks, a lot of new database technologies have been proposed. However, it comes to be a critical problem that researchers are difficult to evaluate their algorithms on current DBMS. People usually have to design and implement different simulating tools to verify the new algorithms on flash disks, and this brings much hard and redundant work. In this paper, we aim at providing a common simulating tool for the evaluation of new algorithms on flash disks. The new tool, named Flash-DBSim, is designed to be reusable and flexible for other researchers to reduce their redundant work. After a brief introduction on the architecture of Flash-DBSim, we present the implemental details of Flash-DBSim. Then, we give a sample use of Flash-DBSim, which aims at evaluating the B+ tree and linear hash index on flash disks. The results show that Flash-DBSim is easy to reconfigure to evaluate the I/O performance of algorithms on flash disks.